Kant and the Role(s) of Doctrines of Methods (Journal of Transcendental Philosophy)

Your Smartphone Is Watching You - Eine technikkritische Untersuchung der menschlichen Freiheit und Antiquiertheit im Zeitalter der Digitaltechnologie - Mac Award, Daria-Leona

The History of the Concept of Truth-making - Milkov, Nikolay (Philosophy Study)

The History of the Concept of Truth-making - Milkov, Nikolay (Philosophy Study)

Hermann Lotze’s Influence on the Twentieth Century Philosophy - Milkov, Nikolay

Bertrand Russell’s Philosophical Logic and its Logical Forms - Milkov, Nikolay (Athens Journal of Philosophy)
From 1901 to 1919, Russell persistently maintained that there were two kinds of logic and distinguished between one and the other as mathematical logic and philosophical logic. In this paper, we discuss the concept of philosophical logic, as used by Russell. This was only a tentative program that Russell did not clarify in detail; therefore, our task will be to make it explicit. We shall show that there are three (-and-a-half) kinds of Russellian philosophical logic: (i) “pure logic”; (ii) philosophical logic investigating the logical forms of propositions; (iii) philosophical logic exploring the logical forms of facts: in epistemology and in the external world. In particular, Russell’s program or philosophical logic of the facts of the external world remained less than sketchily outlined.
Keywords: Russell; mathematical logic; philosophical logic; Wittgenstein

Simmels Abhandlungen zu Kant - Luft, Sebastian (Simmel-Handbuch)

Cassirer’s Children, Special Topics Issue
Keywords: General Medicine

Wilhelm Windelband. Präludien

»Wir hören Dich nicht, schalte bitte Dein Mikro an ! « Einige Gedanken zur digitalen Lehre in der Pandemie. - Luft, Sebastian
Auch in diesem Semester finden Veranstaltungen im Fach Philosophie an den meisten Universitäten vor allem online statt; die Pandemie-Lage lässt eine Öffnung der Unis für Präsenzveranstaltungen kaum zu. Die folgenden Überlegungen hat Sebastian Luft, Professor an der Marquette University in Milwaukee/WI, aus aktuellem Anlass verfasst. 2019 erschien sein Buch »Philosophie lehren« zur philosophischen Hochschuldidaktik. Der folgende Text bietet eine aktuelle Ergänzung zur dortigen Handreichung für die philosophische Lehre.

In Amerika promovieren? Hinweise von Sebastian Luft - Luft, Sebastian (Information Philosophie)

Die angebliche Frage nach dem ‘Sein des Seienden’: An Unknown Husserlian Response to Heidegger’s ‘Question of Being’ - Luft, Sebastian; Janes, Jered (Transcending Reason. Heidegger on Rationality,)

The Space of Culture. Towards a Transcendental Philosophy of Culture Following the Marburg School of Neo-Kantianism (Cohen, Natorp, Cassirer). - Luft, Sebastian

Philosophie Lehren - Luft, Sebastian

Phenomenology without Foundations = Pragmatism? Or: What is Left of Phenomenology After a Pragmatic Critique - Luft, Sebastian (Phänomenologische Forschungen)
This essay attempts to spell out what might be left of Husserlian phenomenology when one leaves behind Husserl’s own grounding ambitions. Husserl construes transcendental phenomenology as first philosophy. In a pragmatist vein of leaving it behind in the interest of something other, I discuss what would happen if one were to ‘pragmatize’ phenomenology. After first laying out Husserl’s vision, in a second part I reconstruct the motives that led to it in reaction to a ‘Cartesian anxiety’ of not securing an indubitable ground of knowledge. After that, the article spells out some pragmatic reflections on what phenomenology would be, without the need to secure foundations of knowledge. Such a liberation would in effect enable phenomenology to more fully make true on the ideals of the Enlightenment (which Rorty, too, underwrites) of emancipating oneself of one of the last vestiges of a dogmatic slumber.

Subjectivity and Lifeworld in Transcendental Phenomenology - Luft, Sebastian

Windelbands Konzeption von Kulturphilosophie und ihr Bezug zur Kulturphilosophie - Luft, Sebastian (Windelband – a Centenary)
This paper presents a comparison between the conception of culture in Windelband and among the Marburg Neo-Kantians. While the latters' concept of culture cannot be understood without assuming a teleology (»infinite task«), Windelband does without such an assumption. His conception of culture is static because, from his point of view, the establishment of norms is possible at any time and in any situation, and therefore it can always lead to a »reasonable regressus to the unreasonable,« i. e., to the establishment of a comprehensive worldview. Philosophy has the task of providing an orientation in crises that arise when a worldview is missing or decaying.

Kulturphilosophie als „naturalistische“ Transzendentalphilosophie und die Frage nach dem Ort der Kultur - Luft, Sebastian (Kultur - Interdisziplinäre Zugänge)

Husserl-Handbuch

Husserl-Handbuch